Kajian Teknis Alat Muat dan Alat Angkut Untuk Memenuhi Target Produksi Pada Penambangan di PT Hillconjaya Sakti Jobsite PT Weda Bay Nickel, Lelilef, Halmahera Tengah, Maluku Utara - Damanik, Lewi Agri Syebat; Inmarlinianto, Inmarlinianto; Nusanto, Gunawan; Waluyo Adji, Dwi Poetranto; Saputro, Kristanto Jiwo (Jurnal Teknologi Pertambangan, 2025)
PT. Hillconjaya Sakti is a company that focuses on the nickel ore mining industry sector. This company is located in Lelilef Village, Weda Tengah District, Central Halmahera Regency, North Maluku Province. PT. Hillconjaya Sakti has a production target of 115,000 tons/month for one working fleet to transport nickel ore from the mining front to the stockpile/TOS. In nickel ore mining activities, mechanical equipment is needed such as loading equipment and transportation equipment. Production produced by loading equipment was 105.834,33 tons/month or 92,03% of the production target, while articulated dump trucks reached 94.237,80 tons/month or 81,95% of the production target. From these production results it can be seen It was concluded that production achievement had not met the target, so it was necessary to study the performance of loading and conveying equipment in nickel ore mining activities so that the company's desired targets could be achieved. The results of the research obtained suggestions for problems to increase production in February 2024 by increasing effective working time. Improving effective working time is carried out by suppressing obstacles that occur and cleaning up residual material on the side of the road to widen the road so that there is a reduction in the circulation time of mechanical equipment. The productivity value of loading equipment after repairs has increased from 105,834.33 tons/month to 134.281,08 tons/month and transportation equipment from 94,237.80 tons/month to 134.087,19 tons/month so that it has met theproduction target set by the company, which is equal to 115,000 tons/month in February.